Cognitive mechanisms in cannabis-related paranoia; Initial testing and model proposal. Issue 4 (1st October 2020) - Newman-Taylor, Katherine; Richardson, Thomas; Sood, Monica; Sopp, Mat; Perry, Emma; Bolderston, Helen
ABSTRACT: Cannabis use can increase severity of symptoms and risk of relapse for people with psychosis. Childhood sexual abuse and high schizotypy increase the risk further. The mechanisms involved remain unclear, and this limits psychological therapies. In three linked studies, we examined the role of two candidate mechanisms – external attribution and cognitive fusion. Study 1 examined these processes in a general population sample and showed that paranoia, psychotic-type experiences, and linked distress were higher in cannabis-users, and mediated by cognitive fusion but not external attribution. Study 2 examined the impact of established risk factors in general population cannabis-users and showed that external attribution and cognitive fusion partially or fully accounted for the effects of childhood sexual abuse and schizotypy on paranoia, psychotic-type experiences and linked distress. Study 3 examined these same processes in a clinical population of people with psychosis and found that external attribution and cognitive fusion partially or fully accounted for the impact of gender, age of first use, sexual abuse and schizotypy. External attribution and cognitive fusion may be key mechanisms in the maintenance of cannabis-related paranoia and account for the impact of established risk factors. We present a cognitive model incorporating these processes to inform clinical practice.